The effect of different times and numbers of Oxfendazole medications in Nelore calves in Goiás State, Brazil - Carneiro, José Roberto; Pereira, Edson; Calil, Fuad; Ferreira, Wanderson Alves; Rocha, Ivo Ponciano (Pesquisa Agropecuaria Brasileira, 2014)
A trial was carried out in cattle to compare the efficacy of Oxfendazole given at different seasons and number of Oxfendazole doses and assessed in terms of antihelminthic activity and live weight gain. Eighty beef cattle (Bos indicus of the Nelore breed) between twelve and 18 months of age were allocated to form groups each of twenty animals. Three of the groups received Oxfendazole at a dose rate of 2.5 mg per kg body weight at a frequency of: once every two months (Group 1), once every 3 months (Group 2) and once every 6 months (Group 3) throughout the course of one year. The remaining animals (Group 4) served as untreated controls. During the trial the animals were weighted and egg count per g of faeces (EPG) was determined monthly. The results showed that the weight gain for all treated groups was greater than that of the controls and that the worm burden was less. As regards the treated groups there was no significant difference among the results from the different dosage regimes during the rainy season. However during the dry season the greatest weight gain and smallest EPG were associated with the application of Oxfendazole once every three months. Quarterly antihelminthic treatment is recomended in order to be economically feasible.